2006
DOI: 10.1002/polb.21018
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between unfolded configurations of proteins and dynamics of folding to the native state

Abstract: ABSTRACT:We compare folding trajectories of chymotrypsin inhibitor (CI2) using a dynamic Monte Carlo scheme with Go-type potentials. The model considers the four backbone atoms of each residue and a sphere centered around C b the diameter of which is chosen according to the type of the side group. Bond lengths and bond angles are kept fixed. Folding trajectories are obtained by giving random increments to the u and w torsion angles with some bias toward the native state. Excluded volume effects are considered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…For example, a recent study of molecular dynamics folding trajectories found that randomly generated chains folded more slowly and less efficiently than chains generated with native-like conformations determined by a knowledge-based potential. 31 This indicates that not all conformations in the unfolded state are equally likely to proceed to the folded state and that there may in fact be specific bottlenecks for leaving the unfolded basin. However, that study did not examine how realistic or probabilistic the productive unfolded conformations are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study of molecular dynamics folding trajectories found that randomly generated chains folded more slowly and less efficiently than chains generated with native-like conformations determined by a knowledge-based potential. 31 This indicates that not all conformations in the unfolded state are equally likely to proceed to the folded state and that there may in fact be specific bottlenecks for leaving the unfolded basin. However, that study did not examine how realistic or probabilistic the productive unfolded conformations are.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we believe this method of reweighting wormlike chain distributions to account for intrachain interactions is robust, realistic, and predictive and may be a useful starting point for further models of protein folding. For example, a recent study of molecular dynamics folding trajectories found that randomly generated chains folded more slowly and less efficiently than chains generated with native-like conformations determined by a knowledge-based potential . This indicates that not all conformations in the unfolded state are equally likely to proceed to the folded state and that there may in fact be specific bottlenecks for leaving the unfolded basin.…”
Section: Discussionmentioning
confidence: 99%